Behaviour in Insurance; the Determinants or Risk Attitudes - Willis, John (2009)
The purpose of this dissertation is to examine the relationship between demographic characteristics and individual risk attitudes in insurance, more specifically, in behaviour relating to willingness to litigate or settle in a car insurance setting. For this purpose, primary data was collected via distribution of a survey which incorporated a measure of risk attitudes set in the context of the post-insurance settlement versus litigation decision faced by an individual after a crash and employed the Holt-Laury mechanism for eliciting individual attitudes to risk. This dissertation therefore answers the call by Doerpinghaus, Schmit, and Yeh (2008) for further research into decisions made by individuals at various stages of the claim negotiations process. For a sample that was risk averse on average, a systematic tendency for enthusiasts to display less risk averse behaviour in comparison to regular car users is found when these individuals make decisions relating to their car. In addition to this and consistent with the majority of previous literature, I find certain demographic characteristics to be significant determinants of variations in risk attitudes. For example, the oft studied factors such as age and gender. The implications for these findings for insurance and future research are discussed.